Early Bereavement Psychosocial Outcomes in Parents of Children Who Died of Cancer With a Focus on Social Functioning. Issue 4 (1st April 2023) - Snaman, Jennifer M.; Mazzola, Emanuele; Helton, Gabrielle; Feifer, Deborah; Morris, Sue E.; Clark, Lisa; Baker, Justin N.; Wolfe, Joanne
Abstract : PURPOSE: The early grief experience of parents of children who died of cancer remains understudied. Understanding psychosocial symptomology and functioning of parents early in their bereavement is essential to developing supportive interventions aimed at offsetting poor mental and physical outcomes. METHODS: Parents of children from two centers who died of cancer 6 to 24 months before were mailed a survey that included validated tools and additional Likert scale-based questions. We used correlation and univariate and multiple regression analyses to assess the associations between psychosocial and grief outcomes and parental social functioning. RESULTS: One hundred twenty-five parents representing 88 children completed the survey. Most respondents identified as female (63%), White (84%), and non-Hispanic (91%). The mean time since child's death was 14.7 (range, 8-26) months. Bereaved parents' mean score for social functioning was only slightly below normative values, and most parents indicated post-traumatic growth and adaptive coping. Parents had high symptom levels for depression, anxiety, post-traumatic stress, and prolonged grief, with those identifying as female having significantly higher symptom scores. Using multivariate analysis, parental scores for resilience and continuing bonds were associated with higher social functioning scores and parental scores for depressive symptoms and prolonged grief were associated with lower social functioning scores. CONCLUSION: Although bereaved parents exhibit resilience and positive coping, they also show high levels of psychosocial distress in the first 2 years after their child's death, which may reflect the typical parental bereavement experience. Screening for low parental social functioning may identify parents who would benefit from additional support early in bereavement.